Multi-professional staff development programme for PAMs...professions allied to medicine - Wray N (International Journal of Language & Communication Disorders)
A unique, accredited, multi-professional education programme for junior staff in professions allied to medicine (PAMs) developed by Durham and Teesside Education and Training Consortium in collaboration with local trusts and social services is described. Designed to ensure competence to practice in line with clinical governance, it aims to strengthen multi-professional working practice through a greater understanding of roles and of the way the national health service (NHS) works. It enables staff to analyse their own learning needs and to employ self-directed learning skills for life-long learning. Using problem-based learning, it uses real clinical cases as triggers to promote critical evaluation and reasoning and the development of multi-professional care pathways.